2011
DOI: 10.1208/s12248-011-9293-6
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Quantitative Disease–Drug–Trial Models for Parkinson’s Disease to Guide Early Drug Development

Abstract: The problem we have faced in drug development is in its efficiency. Almost a half of registration trials are reported to fail mainly because pharmaceutical companies employ one-size-fits-all development strategies. Our own experience at the regulatory agency suggests that failure to utilize prior experience or knowledge from previous trials also accounts for trial failure. Prior knowledge refers to both drug-specific and nonspecific information such as placebo effect and the disease course. The information gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Lee and Gobburu modeled UPDRS as change from baseline at each visit, rather than raw scores, using linear and monomolecular functions analogous to the Guimaraes et al and Bhattaram et al models (Table ) . The focus of their article was to use Bayesian inference to quantify disease progression parameters, that is, to use prior estimates of UPDRS changes from one clinical trial to quantify UPDRS changes from another trial to limit the uncertainty in parameter estimates.…”
Section: Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…Lee and Gobburu modeled UPDRS as change from baseline at each visit, rather than raw scores, using linear and monomolecular functions analogous to the Guimaraes et al and Bhattaram et al models (Table ) . The focus of their article was to use Bayesian inference to quantify disease progression parameters, that is, to use prior estimates of UPDRS changes from one clinical trial to quantify UPDRS changes from another trial to limit the uncertainty in parameter estimates.…”
Section: Literature Searchmentioning
confidence: 99%
“…In each PD model article, the authors demonstrated how disease progression models could be incorporated into designing or analyzing clinical trials. For example, some of the authors used the models to generate data to simulate a clinical trial . Because the models reflect data and there is some knowledge of their error, one can simulate many trials to calculate power and sample sizes and to estimate the treatment effects of pharmacologic agents on disease progression.…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…One common theme that consistently has shown to “de‐risk” drug development is the application of prior knowledge regarding drug‐specific properties and disease‐specific phenomena using quantitative translational methods. Quantitative disease‐drug‐trial models have been recently used in neuropsychiatry to mathematically represent the time course of a disease, placebo effect, a drug's pharmacologic effect, and trial characteristics to guide drug development and regulatory decision making . Examples of the use of disease‐drug‐trials in psychiatry include the longitudinal evaluation of changes in Positive and Negative Syndrome Scale scores for proper comparison of clinically relevant treatment effects, the development of a placebo‐dropout model using Young Mania Rating Scale scores in patients with bipolar disorder to inform future trial design, and the use of the Hamilton Rating Scale for Depression scores to forecast the probability of being a placebo responder …”
mentioning
confidence: 99%
“…Quantitative disease-drug-trial models have been recently used in neuropsychiatry to mathematically represent the time course of a disease, placebo effect, a drug's pharmacologic effect, and trial characteristics to guide drug development and regulatory decision making. 4,5 Examples of the use of disease-drug-trials in psychiatry include the longitudinal evaluation of changes in Positive and Negative Syndrome Scale scores for proper comparison of clinically relevant treatment effects, the development of a placebo-dropout model using Young Mania Rating Scale scores in patients with bipolar disorder to inform future trial design, and the use of the Hamilton Rating Scale for Depression scores to forecast the probability of being a placebo responder. [6][7][8] Binge eating disorder (BED) is a psychiatric disorder characterized by recurrent and distressing binge-eating episodes, defined as eating unusually large quantities of food with a sense of lack of control over eating, without inappropriate compensatory weight loss behaviors.…”
mentioning
confidence: 99%